Metabolic stress-induced human beta-cell death is mediated by increased intracellular levels of adenosine - Ngamjariyawat, Anongnad; Cen, Jing; Said, Romain; Incedal, Ceren; Idevall-Hagren, Olof; Welsh, Nils (Frontiers in Endocrinology, 2023)
High intracellular concentrations of adenosine and 2’-deoxyadenosine have been suggested to be an important mediator of cell death. The aim of the present study was to characterize adenosine-induced death in insulin-producing beta-cells, at control and high glucose + palmitate-induced stress conditions. For this purpose, we treated human insulin-producing EndoC-betaH1 cells with adenosine, 2’-deoxyadenosine, inosine and high glucose + sodium palmitate, and studied death rates using flow cytometry. We observed that adenosine and the non-receptor-activating analogue 2-deoxyadenosine, but not the adenosine deamination product inosine, promoted beta-cell apoptosis at concentrations exceeding maximal adenosine-receptor stimulating concentrations. Both adenosine and inosine were efficiently taken up by EndoC-betaH1 cells, and inosine counteracted the cell death promoting effect of adenosine by competing with adenosine for uptake. Both adenosine and 2’-deoxyadenosine promptly reduced insulin-stimulated production of plasma membrane PI(3,4,5)P3, an effect that was reversed upon wash out of adenosine. In line with this, adenosine, but not inosine, rapidly diminished Akt phosphorylation. Both pharmacological Bax inhibition and Akt activation blocked adenosine-induced beta-cell apoptosis, indicating that adenosine/2’-deoxyadenosine inhibits the PI3K/Akt/BAD anti-apoptotic pathway. High glucose + palmitate-induced cell death was paralleled by increased intracellular adenosine and inosine levels. Overexpression of adenosine deaminase-1 (ADA1) in EndoC-betaH1 cells, which increased Akt phosphorylation, prevented both adenosine-induced apoptosis and high glucose + palmitate-induced necrosis. ADA2 overexpression not only failed to protect against adenosine and high glucose + palmitate-activated cell death, but instead potentiated the apoptosis-stimulating effect of adenosine. In line with this, ADA1 overexpression increased inosine production from adenosine-exposed cells, whereas ADA2 did not. Knockdown of ADA1 resulted in increased cell death rates in response to both adenosine and high glucose + palmitate. Inhibition of miR-30e-3p binding to the ADA1 mRNA 3’-UTR promoted the opposite effects on cell death rates and reduced intracellular adenosine contents. It is concluded that intracellular adenosine/2’-deoxyadenosine regulates negatively the PI3K pathway and is therefore an important mediator of beta-cell apoptosis. Adenosine levels are controlled, at least in part, by ADA1, and strategies to upregulate ADA1 activity, during conditions of metabolic stress, could be useful in attempts to preserve beta-cell mass in diabetes.